Centrality Asymmetry and Partner Complementarity as Influences on Alliance Dissolution. (23rd October 2020) - Hu, Tianyou; Jain, Amit; Delios, Andrew
Abstract: Research on interfirm alliances indicates that partner firms' asymmetry in network centrality increases the likelihood of alliance dissolution because it gives rise to a power imbalance and opportunism in the partnership. We contend that this view of centrality asymmetry does not consider the binding force that network resource complementarity can provide in an alliance, which motivates partners to ally for the long term. We propose that centrality asymmetry can have both divisive and cohesive forces in an alliance, which – when considered together – lead to a prediction that centrality asymmetry has a U‐shaped relationship with alliance dissolution. Moderate levels of asymmetry lead to lower rates of dissolution than high and low levels of asymmetry. The degree of cooperation between partners and the degree of external competition reduce the effects of centrality asymmetry on alliance dissolution because they mitigate power imbalances while encouraging partners to strengthen the alliance to withstand competitive challenges.